COMPARISON OF THE EFFECTIVENESS OF RAW AMBON BANANA MOSS (MUSA ACUMINATA) AND 10% POVIDONE IODINE IN CONTROLLING BACTERIA IN CONTAMINATED WOUNDS WHAT TO DO WITH MICE WHITE (WISTAR STRAIN) - Laila Nur Fadhilah; Muhasim Muhasim (STIKes Kepanjen, 2022)
Povidone Iodine has become the most famous antiseptic that were used for century although still having some toxic and corrosive effect to the cell, which in the worst condition can cause kidney failure. Unripe ambon lumut banana peels (Musa acuminata) were having chemical compounds which able to inhibit the bacterial growth that can be a safer alternative antiseptic beside Povidone Iodine. The purpose of this study is to determine the comparison of effectiveness of unripe ambon lumut banana peels (Musa acuminata) and Povidone Iodine 10% in controlling bacteria of contaminated wounds on white rats (Wistar strain). True experimental design were used in this research. 25 rats used as the sample. Data obtained were analized with One Way Anova and Post Hoc test. As a result, it showed that there were differences between concentration of unripe ambon lumut banana peels extract and Povidone Iodine 10% to the bacteria reduction (p=0,038). In the concentration of 90%, unripe ambon lumut banana peels extract were able to reduce the bacteria with an average of 477 CFU while povidone iodine 10% only reduce 333 CFU. It’s conclude that the application of unripe ambon lumut banana peels (Musa acuminata) extract in the concentration of 90% was giving higher effectiveness in controlling the growth of bacteria rather than povidone iodine 10%.